GE_GERICHTE P/13932/2011 vom 2. November 2011 - GE Cour de justice (2011)
; SOUPÇON ; PREUVE ILLICITE ; DÉFENSE NÉCESSAIRE ; CONFRONTATION ; JONCTION DE CAUSES ; DROIT DE GARDER LE SILENCE | CPP.113; CPP.30; CPP.221; CPP.158; CPP.140; CPP.130; CPP.141; CPP.146; CPP.147